PERAN KEPALA MADRASAH SEBAGAI MANAJER DALAM PENGINTEGRASIAN PENDIDIKAN KARAKTER - Muhammad Suhardi; Rifma Rifma; Syahril Syahril (Jurnal Dedikasi Pendidikan, 2022)
The economic progress and information technology achieved have not been directly proportional to creating a civilized society. This civil society applies noble values in life such as being honest, straightforward, tolerant, disciplined, respecting human rights, and being responsible. The madrasah principal is an educational component that is very important in determining and creating the quality of madrasa education in general, including in terms of designing, designing, implementing, and at the same time evaluating character education programs in line with the renewal of the duties and functions of the new madrasah principal as manager, entrepreneur, and supervisor. In madrasas, the revitalization of the role of madrasah principals in the implementation of character education in madrasas is very much needed. The head of the madrasa is no longer an additional task but purely as a manager, supervisor, and innovator in his work environment. This study aims to conceptually find out how the duties of a madrasa principal as a manager in his school are in designing, monitoring, and reinforcing the integration of character strengthening in everyday life in madrasah.